Marine diesel selective catalytic reduction urea injection system - GU JIAQI; XIA JUHUA; SHEN TENG; CHEN XIAOLEI; HOU CHUNGUO; XU JUN; CHENG QI (2017)
The utility model provides a marine diesel selective catalytic reduction urea injection system, contains pump package unit, air unit and measurement unit, and this system can automatic control urea injection quantity and spraying pressure, makes urea solution mix with nitrogen oxide fully, realizes the abundant reaction of reductant and catalyst. It normally works to guarantee the reactor of marine diesel's nitrogen oxide NOX reduction of discharging system. Urea solution's pressure maintaining is invariable in messenger's pipeline, guarantees the stability of diesel engine SCR system operation under the different work condition condition. When the bring to rest of SCR system, urea injection system can sweep, prevent the jam of pipeline and nozzle, extension injection system's life. 种船用柴油机选择性催化还原尿素喷射系统，包含泵组单元、空气单元和计量单元，该系统能够自动控制尿素喷射量及喷射压力，使尿素溶液充分地与氮氧化物混合，实现还原剂与催化剂的充分反应。保证船用柴油机的氮氧化物NO减排系统的反应器正常工作。使管道中尿素溶液的压力维持恒定，保证柴油机在不同工况条件下SCR系统运行的稳定性。在SCR系统停止运行时，可以吹扫尿素喷射系统，防止管路及喷嘴的堵塞，延长喷射系统的使用寿命。